Perceived Healthfulness, Nutrient Content Awareness, Consumption, and Intention to Purchase Selected Ultraprocessed Products Among Adults in South Africa - Makoma Bopape; Jeroen De Man; Lindsey Smith Taillie; Rina Swart (Advances in Public Health)
Conclusion and Implications: Intervention strategies such as simplified front-of-pack labeling may have a role in improving nutrition awareness and discouraging UPP consumption.